Determinants of default from full completion of vaccination among children between 12 and 23 months old in Yilmana Densa district, west Gojam zone, Ethiopia, 2019 - Mekuria, Desalegn Koyto; Hailu, Getachew; Bedimo, Melkamu; Tefera, Alemu Adela (Frontiers in Public Health, 2022)
Background Vaccination is one of the best cost-effective public health interventions to safeguard children from vaccine-preventable diseases. In Ethiopia, the prevalence of default to the full completion of child immunization is high. However, the determinants of default to full completion have not been thoroughly investigated in this study area. Therefore, this study assessed the determinants of default to the full compilation of vaccination among children between 12 and 23 months old in Yilmana Densa District, west Gojam, northwest Ethiopia. Methods A community-based unmatched case-control study design was employed in the Yilmana Densa district among 343 (111 cases and 232 controls) randomly selected 12–23 months old children. Face-to-face interviews were used to collect data using a multistage sampling method. For analysis, data were entered into epidata version 3.1 and exported to SPSS 23 software. Descriptive analysis followed by binary and multivariable logistic regression analysis was conducted. The statistical significance was declared at a p-value of 0.05. Result This study identified that mothers who had not attended ANC follow-up [AOR = 5.55, 95% CI: (1.789–17.217)], mothers who had not gotten information about vaccinations [AOR = 8.589, 95% CI: (4.414–16.714)], and mothers whose time taken to reach vaccination site is more than 39 min were at higher risk to default from completion of vaccination [AOR = 3.252, 95% CI: (1.952–5.417)]. Furthermore, maternal waiting time (>45 min) for child vaccination [AOR = 2.674, 95% CI: (1.517–4.714)] and home delivery [AOR 3.19, 95% CI: (1.751–5.814)] were risk factors to default child from full completion of vaccination. Conclusion Mothers delivered at home, mothers not attending ANC follow-up, mothers who did not get health information about the vaccine, mothers taking longer time to reach the vaccination site, and staying longer time for child vaccination are causes of default. Motivated institutional delivery services utilization is recommended. The district office should consider the distribution of vaccination sites by the opening of new outreach site to reduce the waiting time of mothers.